Multi-stress aging investigations of HTV silicone rubber filled with Silica/ATH composites for HVAC and HVDC transmission. (March 2020) - Akbar, Muhammad; Ullah, Rahmat; Qazi, Ibrahim
Highlights: SR composites are investigated for long term performance under AC and DC voltages. All the samples were exposed to multi-stress aging for a period of 5000 h. Different diagnostics techniques were deployed to assess aging behavior. Degradation under DC were more severe due to the unidirectional stress as compared to AC stress. Abstract: Multi-stress aging performance of high-temperature-vulcanized-silicone rubber (HTV-SR) composites was investigated in a simulated environment separately both under AC and DC voltages. Two specially designed weathering chambers were fabricated one each for AC and DC voltages. Four type of SR-composites filled with varying amount of nano-silica and micro aluminum-tri-hydrate (ATH) were exposed to multi-stress aging spanning over a period of 5000 h. The test samples were designated as TS1, TS2, TS3 and TS4. The parameters of weather cycle were designed representing a prevailing local environment which is of great interest of operating electric utility company in the context of pollution severity. Different well-defined evaluation methods and diagnostic techniques were employed to understand aging behavior of each test samples. The surface wettability was evaluated using the Swedish Transmission Research Institute (STRI) classification method and through contact angle measurements. Leakage current was measured after each aging cycle to assess degree of surface aging. Fourier Transform Infrared (FTIR) spectroscopy was employed to identify and examine molecular-level changes in the material and a Scanning Electron Microscopy (SEM) was utilized to analyze the morphological changes in the HTV-SR. Mechanical properties of each sample were checked by measuring its tensile strength and elongation-at-break as well as through shore-A hardness tests. The study revealed that exposure to multi-stress aging caused de-polymerization, loss of hydrophobicity and material degradation of the test sample. The DC-stressed samples showed 20% to 30% higher degradation compared with their AC-stressed counterparts while other environmental stresses were maintained identical. This behavior is attributable to more detrimental effect of unidirectional DC stress. Having conducted overall assessment of aging, we found that among the various investigated samples, the TS2 exhibited maximum resistance to aging. These results are thoroughly presented in this paper.